The Political Process of Bureaucratic Reform (Study on Bandung City Government in 2015) - Andrian, Andrian (Budapest International Research and Critics University, 2022)
This study analyzes the political process of bureaucratic reform of the Bandung city local government in 2015. This research based on bureaucratic reform in the Bandung City government has received an excellent predicate from the Ministry of State Apparatus Empowerment and Bureaucratic Reform. This is due to the similarity ofperceptions between the Bandung City government and the DPRD. This study aims to explore the political process built by the Bandung City government and the DPRD in developing the city of Bandung through bureaucratic reform. The research method used in this study is a qualitative approach with a case study method. The result of this study is that Ridwan Kamil as the Mayor of Bandung has a strong desire to make significant changes through a digitalization-based government performance system. Obviously to achieve such targets requires the support of politicians and elements of society. Therefore, the executive and the DPRD along with the SKPD and community elements sat together in the discussion of the bureaucratic reform. In the end, the move received mutual approval.